Permanent His-bundle pacing: a systematic literature review and meta-analysis. Issue 11 (26th April 2018) - Zanon, Francesco; Ellenbogen, Kenneth A; Dandamudi, Gopi; Sharma, Parikshit S; Huang, Weijian; Lustgarten, Daniel L; Tung, Roderick; Tada, Hiroshi; Koneru, Jayanthi N; Bergemann, Tracy; Fagan, Dedra H; Hudnall, John Harrison; et al.
Abstract: Aims: Permanent cardiac pacing of the His-bundle restores and retains normal electrical activation of the ventricles. Data on His-bundle pacing (HBP) are largely limited to small single-centre reports, and clinical benefits and risks have not been systematically examined. We sought to systematically examine published studies of patients undergoing permanent HBP and quantify the benefits and risks of the therapy. Methods and results: PubMed, Embase, and Cochrane Library were searched for full-text articles on permanent HBP. Clinical outcomes of interest included implant success rate, procedural and lead complications, pacing thresholds, QRS duration, and ejection fraction at follow-up, and mortality. Data were extracted and summarized. Where possible, meta-analysis of aggregate data was performed. Out of 2876 articles, 26 met the inclusion criteria representing 1438 patients with an implant attempt. Average age of patients was 73 years and 62.1% were implanted due to atrioventricular block. Overall average implant success rate was 84.8% and was higher with use of catheter-delivered systems (92.1%; P < 0.001). Average pacing thresholds were 1.71 V at implant and 1.79 V at >3 months follow-up; although, pulse widths varied at testing. Average left ventricular ejection fractions (LVEFs) were 42.8% at baseline and 49.5% at follow-up. There were 43 complications observed in 907 patients across the 17 studies that reported safety information. Conclusion: Among 26 articles of permanent HBP, the implant success rate averaged 84.8% and LVEF improved by an average of 5.9% during follow-up. Specific reporting of our clinical outcomes of interest varied widely, highlighting the need for uniform reporting in future HBP trials.